PECULIARITIES OF JOINT PATROLLING AT THE LITHUANIAN-POLISH STATE BORDER - Lepeška, Antanas (Border Security and Management, 2023)
Lithuanian border guards carry out joint patrols with officials of both neighboring European Union countries – Poland and Latvia. And although the legal basis is similar, the practical implementation of joint patrols is significantly different. In this article, the author introduces the joint patrol on the Lithuanian-Polish state border carried out by the officers of the State Border Guard Service. A historical overview of joint patrolling is provided. The training system for joint patrol officers is explained and an overview of the previous training has been presented. Aspects of the legal regulation and practical activities of the joint patrols carried out by the officers of the Lithuanian and Polish border guard services are analyzed. Good practice and issues are presented. It is suggested how to improve the efficiency of joint patrol training and improve the implementation of joint patrolling.